10.1001/jama.2012.5833.test (CrossRef Listing of Deleted DOIs, 2000)
Importance In a phase 2 randomized clinical trial, high-dose vitamin D3 added to standard treatment improved progression-free survival (PFS) compared with standard-dose vitamin D3 in patients with metastatic colorectal cancer (mCRC). Objective To determine if high-dose vitamin D3 added to standard chemotherapy improves outcomes in patients with previously untreated mCRC. Design, setting, and participants Double-blind phase 3 randomized clinical trial enrolling 455 patients with previously untreated mCRC, conducted in the US through the National Clinical Trials Network from October 2019 to December 2022 (database freeze: July 15, 2024). Interventions mFOLFOX6 (modified FOLFOX6 [5-fluorouracil, leucovorin, oxaliplatin]) or FOLFIRI (5-fluorouracil, leucovorin, irinotecan) plus bevacizumab every 2 weeks with either high-dose vitamin D3 (8000 IU daily × 14 days as loading dose followed by 4000 IU daily) or standard-dose vitamin D3 (400 IU daily) until disease progression, intolerable toxicity, or withdrawal of consent. Main outcomes and measures The primary end point was PFS assessed by the unstratified log-rank test. Secondary end points included objective response rate, overall survival, and toxicity. Prespecified subgroup analyses of PFS were performed according to known prognostic factors. Results Among 455 randomized patients (median age, 59 years; 181 [40%] female) with median follow-up 20 months, the median PFS for high-dose vitamin D3 (n = 228) was 11.8 months (95% CI, 10.3-13.3) vs 10.3 months (95% CI, 9.4-12.2) for standard-dose vitamin D3 (n = 227) (1-sided log-rank P = .25). There were no significant differences in objective response rate between high-dose and standard-dose vitamin D3 (51% [95% CI, 44%-58%] vs 44% [95% CI, 37%-50%], respectively; P = .12), or in overall survival (median, 25.6 vs 27.0 months; 1-sided log-rank P = .66). There were no clinically meaningful differences in the most common grade 3 or greater adverse events between the high- and standard-dose groups, including neutropenia (n = 67 [32%] vs n = 62 [30%]) and hypertension (n = 42 [20%] vs n = 49 [23%]) or in incidence of vitamin D-associated toxicities. Conclusions and relevance Among patients with previously untreated mCRC, addition of high-dose vitamin D3, vs standard-dose vitamin D3, to standard chemotherapy plus bevacizumab did not improve PFS. Trial registration ClinicalTrials.gov Identifier: NCT04094688.